The effect of rumen inert fat supplementation and protein degradability in starter and finishing diets on veal calf performance and the fatty acid composition of the meat - Lategan, Elna (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.